2010
DOI: 10.3390/molecules15128534
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Activity, Antioxidant Capacity and Tannin Content in Plants of Semi-Arid Northeastern Brazil

Abstract: The objective of this study was to evaluate antiproliferative activity, antioxidant capacity and tannin content in plants from semi-arid northeastern Brazil (Caatinga). For this study, we selected 14 species and we assayed the methanol extracts for antiproliferative activity against the HEp-2 (laryngeal cancer) and NCI-H292 (lung cancer) cell lines using the (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazole) (MTT) method. In addition, the antioxidant activity was evaluated with the DPPH (2,2-diphenyl-2-picry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(48 citation statements)
references
References 23 publications
3
40
0
5
Order By: Relevance
“…Recent interest in tannins has been stimulated by the potential health benefits arising from the antioxidative activity. Good contribution of tannins in antioxidant activity has been observed by Gomes de Melo et al (2010). The results showed that the carotenoids content of L. siceraria, M. charantia and L. cylindrica measured as β-carotene was significantly higher when compared to remaining gourd vegetables (P < 0.05) with M. charantia exhibiting the highest content in all types of extracts.…”
Section: Quantitative Testing Of Phytochemicalsmentioning
confidence: 88%
“…Recent interest in tannins has been stimulated by the potential health benefits arising from the antioxidative activity. Good contribution of tannins in antioxidant activity has been observed by Gomes de Melo et al (2010). The results showed that the carotenoids content of L. siceraria, M. charantia and L. cylindrica measured as β-carotene was significantly higher when compared to remaining gourd vegetables (P < 0.05) with M. charantia exhibiting the highest content in all types of extracts.…”
Section: Quantitative Testing Of Phytochemicalsmentioning
confidence: 88%
“…Stigmasterol and β-sitosterol extracted from S. crispa have been demonstrated to possess anti-cancer effects on liver, breast, and colon carcinoma (22). Other anti-cancer compounds that may be extracted include alkaloids and tannins (20), which have been documented to exhibit anti-cancer properties (37)(38)(39)(40). In order to identify the compounds responsible for the anti-cancer effects, further studies on the isolation and purification of the bioactive compounds from S. crispa are required.…”
Section: Percentage Of Cells ----------------------------------------mentioning
confidence: 99%
“…Dicha capacidad antioxidante se atribuiría al alto contenido de fenoles totales que presenta, esto de acuerdo con estudios previos que indican una relación directa entre actividad antioxidante y contenido de fenoles totales en hierbas, vegetales y frutos (18) , y esta a su vez con el contenido de taninos y su eficiencia antirradical (19,20) . De acuerdo con la clasificación de Gomes de Melo y col. (21) , el EAVT muestra una buena actividad antioxidante, y resultados similares han sido reportados en otros estudios referentes a los extractos de vainas de tara (4,22) . La influencia del medio ambiente, nutrición y genotipo, así como el tiempo de la cosecha y su tratamiento post-cosecha pueden afectar la calidad y niveles de antioxidantes en las plantas.…”
Section: Discussionunclassified